THE IMPLEMENTATION OF DIFFERENTIATED LEARNING INSTRUCTION IN SMP YPS SINGKOLE - Rannu, Ceriati Bahagia; Salija, Kisman; Sulaiman, Iskandar (JTechLP: Journal of Technology in Language Pedagogy, 2023)
This study aims to determine the implementation of Differentiated Learning in institutions. This research is qualitative research with a case study type for collecting data using observation and interviews. The data collected is then analyzed using the Miles and Huberman model techniques, namely through data reduction, data display, and conclusion. The research was conducted at SMP YPS Singkole, Sorowako. The results of the research show: 1) Teachers’ perspectives are encouraged to put differentiated instruction in action, take advantage of individual differences, and ensure every student has fair access to learning opportunities. 2) Differentiated learning instruction is successfully implemented by integrating a variety of strategies, including adapting lessons to accommodate varying learning styles, providing engaging and challenging content, and integrating technology and multimedia to boost engagement and encourage lifelong learning. 3) Differentiated learning instruction prioritizes the needs and unique characteristics of each student, creates a learning environment, and ultimately increases student engagement. The results of the study indicate that there have been efforts by teachers and institutions to apply differentiated learning instruction in learning activities.